Enzyme-catalysed transformations of ent-kaurane diterpenoids - Monsalve, Leandro Nicolas (2005)
Several acetyl derivatives of linearol, atractyligenin and atractylitriol were obtained through enzyme-catalysed acetylation and deacetylation reactions. In most reactions lipases showed regio- and stereoselective behaviour, allowing a family of novel compounds to be prepared.